Understanding how OSS Development Models can influence assessment methods - Taylor, Richard (Electronic Communications of the EASST, 2009)
One of the most important aspects of OSS that distinguishes it from COTS is both the variety and specific characteristics of the development models used. Understanding these development models will be critical to the effective design of assessment approaches. This paper documents the more common development models used by OSS projects and explores the complex landscape of stakeholders that these models expose.